Participatory rangeland management for pastoralist communities - Lyaga, M.; Sircely, Jason A.; Crane, Todd A.; Muigai, S.; Ng'ang'a, Irene N.; Ngome, David; Flintan, Fiona E. (International Livestock Research Institute, 2023)
A cartoon book explaining the steps of particpatory rangeland management (PRM)